2019
DOI: 10.1021/acssuschemeng.9b03425
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Fe2TiO5 Photoanode through Surface Al3+ Treatment and FeOOH Modification

Abstract: Fe2TiO5 is recognized as a novel and promising photoanode material for solar water splitting. Here, nanostructured Fe2TiO5 was fabricated on a fluorine-doped tin oxide substrate by an electrospray deposition technique. We utilized surface Al3+ treatment and FeOOH modification to improve performance of the Fe2TiO5 photoanode. After this two-step enhancement, the photocurrent density of the final Fe2TiO5 photoanode is 0.52 mA cm–2 at 1.23 VRHE which is 2.8 times that of the pristine one, and the onset potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…First, because Fe 2 O 3 and TiO 2 are both very stable and unreactive binary oxides, the ability to synthesize high-quality Fe 2 TiO 5 using our new method demonstrates the method’s efficacy. Second, as mentioned above, Fe 2 TiO 5 has many advantageous features for use as a photoanode; however, investigations of this compound as a single photoanode have been limited. , Therefore, the synthesis of high-quality Fe 2 TiO 5 electrodes also provides us with a great opportunity to systematically examine the photoelectrochemical properties of Fe 2 TiO 5 . Furthermore, we note that although there have been a few theoretical studies on the electronic structure of pristine Fe 2 TiO 5 , polaron formation and the effect of doping on the charge-transport properties of Fe 2 TiO 5 have not been theoretically investigated.…”
Section: Introductionmentioning
confidence: 99%
“…First, because Fe 2 O 3 and TiO 2 are both very stable and unreactive binary oxides, the ability to synthesize high-quality Fe 2 TiO 5 using our new method demonstrates the method’s efficacy. Second, as mentioned above, Fe 2 TiO 5 has many advantageous features for use as a photoanode; however, investigations of this compound as a single photoanode have been limited. , Therefore, the synthesis of high-quality Fe 2 TiO 5 electrodes also provides us with a great opportunity to systematically examine the photoelectrochemical properties of Fe 2 TiO 5 . Furthermore, we note that although there have been a few theoretical studies on the electronic structure of pristine Fe 2 TiO 5 , polaron formation and the effect of doping on the charge-transport properties of Fe 2 TiO 5 have not been theoretically investigated.…”
Section: Introductionmentioning
confidence: 99%
“…This feature can be verified in the diffractograms of the selected NiFeO x /FeTO-S1 and CoFeO x /FeTO-S20 samples (Figure S1), which represent all the other samples prepared in this study, whose patterns are very similar and are not displayed for clarity purposes. [18,20,36,50] As no structural alteration was detected, these patterns point out that the MSD method and the posterior calcination step did not lead to any damage to the original structure and that the pseudobrookite phase of the Fe 2 TiO 5 matrix was maintained.…”
Section: Resultsmentioning
confidence: 79%
“…Kuang et al . reported an electrospray technique for the preparation of Fe 2 TiO 5 photoanodes and posteriorly modified them by surface state passivation with Al 3+ and by FeOOH decoration, showing both approaches were effective in increasing the resulting photocurrent density values to 0.52 mA cm –2 at +1.23 V RHE . Similarly, Wang et al .…”
Section: Introductionmentioning
confidence: 94%
“…13 Kuang et al reported an electrospray technique for the preparation of Fe2TiO5 photoanodes and posteriorly modified them by surface state passivation with Al 3+ and by FeOOH decoration, showing both approaches were effective in increasing the resulting photocurrent density values to 0.52 mA cm -2 at +1.23 VRHE. 14 Similarly, Wang et al carried out a F-surface treatment of Fe2TiO5 and increased photocurrent density values due to formation of Ti-F facilitating hole transfer to the electrolyte. 15 The multi-step deposition of thin layers of Fe2TiO5 on top of TiO2 or α-Fe2O3 has also been researched.…”
Section: Introductionmentioning
confidence: 99%